1995
DOI: 10.1055/s-2007-1013212
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Bioprosthesis Without Early Anticoagulation-Risk of Thromboembolism

Abstract: Anticoagulation after implantation of a bioprosthetic heart valve has been suggested during a high-risk period of 3 months following surgery. There is little information available concerning the risk of thromboembolism during this period if anticoagulation is not carried out. However, this is of interest since 60-80% of all bleeding complications due to anticoagulation occur during the first year of treatment. Between 1983 and 1993, 57 of our patients did not receive oral anticoagulation after implantation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 1 publication
(1 reference statement)
1
14
0
2
Order By: Relevance
“…Among patients with bioprosthetic valves in the aortic position, who received subcutaneous heparin 22,500 IU/d and aspirin 100 mg/d for the first 14 to 22 days after operation, but did not receive oral anticoagulants, the frequency of thromboemboli during the first 6 months was 1 occurrence out of 57 subjects (1.8%). 40 Among patients who received oral anticoagulants and heparin 5,000 U subcutaneously every 12 h, 0 of 109 patients with prosthetic valves in the aortic position had thromboemboli during the first 3 months. 38 However, some showed no advantage of early anticoagulation among patients with bioprosthetic valves in the aortic position.…”
Section: First 3 Months After Insertion In the Aortic Positionmentioning
confidence: 99%
“…Among patients with bioprosthetic valves in the aortic position, who received subcutaneous heparin 22,500 IU/d and aspirin 100 mg/d for the first 14 to 22 days after operation, but did not receive oral anticoagulants, the frequency of thromboemboli during the first 6 months was 1 occurrence out of 57 subjects (1.8%). 40 Among patients who received oral anticoagulants and heparin 5,000 U subcutaneously every 12 h, 0 of 109 patients with prosthetic valves in the aortic position had thromboemboli during the first 3 months. 38 However, some showed no advantage of early anticoagulation among patients with bioprosthetic valves in the aortic position.…”
Section: First 3 Months After Insertion In the Aortic Positionmentioning
confidence: 99%
“…Moinuddeen et al [12] and Babin-Ebell et al [13] showed similar results when assessing patients retrospectively. Brueck et al [14] comparing ASA with no therapy in 288 consecutive patients with sinus rhythm did not find differences in the outcomes of functional status, embolic events and survival with 3 months of aortic bioprosthesis replacement.…”
Section: Discussionmentioning
confidence: 59%
“…5,6 To date, no randomized trials and few retrospective studies have compared the effectiveness of different regimens in preventing postoperative thromboembolism and hemorrhage after BAVR. Babin-Ebell et al 11 and Joyce and Nelson 30 found no benefit in early warfarin therapy compared with ASA and concluded that standard anticoagulation did not seem to be beneficial. Authors of 4 retrospective studies 9,[31][32][33] suggested the use of ASA therapy alone without short-term anticoagulation.…”
Section: Discussionmentioning
confidence: 99%